Wage Shocks and Consumption Variability in Mexico during the 1990s - Miguel Székely; Orazio P. Attanasio (Inter-American Development Bank, Research Department, 2001)
This paper presents evidence on the relationship between economic shocks to relative male wages and changes in household consumption in Mexico during the 1990s, which is a period characterized by high volatility. In addition to performing this type of analysis for Mexico for the first time, the paper makes two main contributions. The first is the use of alternative data sources to construct instrumental variables for wages. The second is to examine differences across four consumption categories: non-durable goods, durable goods, education and health. Our results for non-durable goods consumption reject the hypothesis that Mexican households are able to insure idiosyncratic risk. For the comparisons across consumption categories, the conclusion is that households in Mexico tend to react to temporary shocks by contracting the consumption of goods that represent longer-run investment in human capital, which makes them more vulnerable in the future.
Keywords: 330; Lohn; Schock; Gesamtwirtschaftlicher Konsum; Verbraucherausgaben; Mexiko